Δ13C referential in three Pinus species for a first archaeological application to Paleolithic contexts: "Between intra- and inter-individual variation and carbonization effect". (August 2018) - Audiard, Benjamin; Blasco, Thierry; Brossier, Benoit; Fiorentino, Girolamo; Battipaglia, Giovanna; Théry-Parisot, Isabelle
Abstract: Tree-ring studies, particularly those focusing on the δ 13 C isotopic signal, have become a reliable method to reconstruct past climatic and environmental conditions. Unfortunately, wood remains are notably absent from the very ancient archaeological record, due to degradability of plant tissue. For archaeological studies, the analysis of isotopic signals from charcoal of Pinus species, which is more reliably preserved over time, and continuously represented among archaeological remains, would yield more robust findings. However, methodological confirmation of this approach is required prior to the archaeological implementation of this tool. Here, we present a wood-charcoal reference set, focused on the intra-genus Pinus spp. Δ 13 C data ( Pinus halepensis L., Pinus sylvestris Mill., Pinus nigra subsp. nigra Arn.), which addresses both natural variability and the isotopic impact of the carbonization. Our results show the potential application of an average isotopic signal from different Pinus spp. either from wood and charcoal. Moreover, carbonization results offer a baseline from which to create a general correction of the δ 13 C shift introduced during pyrolysis temperature gradients. Lastly, a primary reference set was established in the context of climatic and environmental parameters for future archaeological analyses of charcoal remains. Highlights: δ 13 C variations areprincipally associated with individual variation rather than differencesbetween species ( Pinus spp.) New data for a correction model δ 13 C changes during carbonization based on the increase of charcoal carbon concentration (%C) No significant difference was observed between Pinus spp. in terms of the impact of carbonization on δ 13 Cpin values Isotopic analyses on charcoal of the genus Pinus from the quaternary period could provide a reliablepaleoclimatic marker